2019
DOI: 10.1186/s12891-019-2968-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glenosphere and baseplate parameters on Glenoid bone strains in reverse shoulder Arthroplasty

Abstract: BackgroundLittle is known about the strains at the glenoid near the bone-implant interface in reverse shoulder arthroplasty. The purpose of the current study was to evaluate the strains on the glenoid bone under a compressive load after implantation of three different sizes of metal-backed baseplates in either inferior or superior position in combination with three different sizes of glenospheres and three different glenosphere designs.MethodsThree sizes of baseplates (small, medium, large) were implanted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Despite contradictory results, most experimental studies preferred an inferior position of the baseplate to increase the peak load failure and improve rotation [56][57][58][59][60][61][62][63]. A retrospective cohort study (n = 54) showed that patients with scapular notching had higher positioned baseplates (as measured from the baseplate's inferior aspect to the inferior rim of the glenoid) than did those without scapular notching (2.8 ± 3.3 vs. 0.6 ± 2.0 mm, P = 0.03, respectively) [64].…”
Section: Baseplate Positionmentioning
confidence: 99%
“…Despite contradictory results, most experimental studies preferred an inferior position of the baseplate to increase the peak load failure and improve rotation [56][57][58][59][60][61][62][63]. A retrospective cohort study (n = 54) showed that patients with scapular notching had higher positioned baseplates (as measured from the baseplate's inferior aspect to the inferior rim of the glenoid) than did those without scapular notching (2.8 ± 3.3 vs. 0.6 ± 2.0 mm, P = 0.03, respectively) [64].…”
Section: Baseplate Positionmentioning
confidence: 99%